Predicting Compulsive Buying Because of Buy Now Pay Later Installment - Rina Sari Qurniawati; Yulfan Arif Nurohman; Dhandy Rachmat Andreyan (University of Darussalam Gontor, 2023)
The Covid-19 pandemic that has hit the whole world since the beginning of 2020 has changed consumer behaviour in shopping. With the development of pay-later payments in Indonesia since this pandemic period, compulsive buying behaviour is influenced by the pain of paying and the ease of payment methods. For this reason, this research has an urgency to be carried out so that people have control over their behaviour. In testing the hypothesis using the SEM-PLS technique by testing the inner model and outer model using 120 samples. The results of this study are the pain of paying and the ease of payment methods proved to affect compulsive buying. Self-control has not been shown to have a moderating effect on the relationship between the pain of paying and compulsive buying.